Body Mass Index Has a Nonlinear Association With Postoperative 30-Day Mortality in Patients Undergoing Craniotomy for Tumors in Men: An Analysis of Data From the ACS NSQIP Database - Liu, Yufei; Hu, Haofei; Han, Yong; Li, Lunzou; Li, Zongyang; Zhang, Liwei; Luo, Zhu; Huang, Guodong; Lan, Zhan (Frontiers in Endocrinology, 2022)
Background: The association between body mass index (BMI) and mortality is controversial. Thus, the purpose of our research was to survey the association between BMI and postoperative 30-day mortality in brain tumor patients undergoing craniotomy. Methods: This study analyzed data collected in a multicenter, cross-sectional study that consecutively and nonselectively collected data from a total of 18,642 patients undergoing craniotomy for tumors in the ACS NSQIP from 2012 to 2015. We constructed three linear and non-linear binomial logistic models (the inflection point was set at 18.5) to evaluate the association between BMI and postoperative 30-day mortality, respectively. We also conducted subgroup analyses. Additionally, we compared non-linear models with vs. without interaction with sex. Results: A total of 17,713 patients were included in this analysis. Of these, 47.38% were male. The postoperative 30-day mortality of the included cases was 2.39% (423/17,713), and the mean BMI was 28.41 ± 6.05 kg/m2. The linear logistic models suggested that after adjusting for the covariates, BMI was not associated with postoperative 30-day mortality (OR=0.999; 95% CI: 0.981, 1.017). The non-linear binomial logistic models suggested a nonlinear relationship between BMI and postoperative 30-day mortality. When BMI was < 18.5, we observed a stronger negative association between them after adjusting for covariates; the OR and 95% CI were 0.719, 0.576-0.896. When BMI was > 18.5, the relationship between them was not significant. We also found that a one-unit decrease in BMI for male patients with BMI < 18.5 kg/m2 was related to a 34.6% increase in the risk of postoperative 30-day mortality (OR=0.654, 95% CI (0.472, 0.907). There was no significant association between them in male patients with BMI > 18.5 kg/m2 or female patients. Conclusions: This study demonstrates a non-linear relationship between BMI and the risk of postoperative death. Preoperative underweight (BMI < 18.5 kg/m2) would increase the risk of postoperative death in male patients (> 18 years old) undergoing craniotomy for brain tumors. Appropriate nutritional management prior to craniotomy for brain tumors may reduce the risk of postoperative 30-day mortality in underweight men.